Informetric Studies on Physics Theses of Indian Institute of Science. By K.G. Sudhier - Harinarayana, N.S. (Journal of Information and Knowledge, 2017)
The abundance of information poses a problem of a different kind just as lack of information does. Comprehending information and filtering it for consumption and decision-making are the major challenges faced by the modern society. Quantitative measurement techniques have been developed and used for the analysis of production and use of information. These techniques are in vogue for a few decades now, and these techniques form the basis for ‘bibliometrics’, ‘informetrics’, ‘scientometrics’, ‘webometrics’ etc. Altmetrics is the new research area added to this group. Purists do make a distinction in the scope and application of these fields of study, although from a student perspective they are overlapping disciplines. It may be mentioned that Indian literature on the subject refers to S.R. Ranganathan who introduced the term ‘librametry’ even before terms such as bibliometrics, informetrics, etc. came into vogue (Sen, 2015)